FAMILY SOCIO-ECONOMIC FACTORS RELATED TO DIETARY DIVERSITY OF CHILDREN AGED 12-23 MONTHS: FAMILY SOCIO-ECONOMIC FACTORS RELATED TO DIETARY DIVERSITY OF CHILDREN AGED 12-23 MONTHS - Khalida Dalimunthe, Nathasa; Ekayanti, Ikeu; Dwiriani, Cesilia Meti (STIKes Mitra Keluarga, 2024)
Background: Nutritional problems in infants and children are the focus of the scaling up nutrition movement or the acceleration of nutrition improvement. Appropriate feeding practices in Indonesia are still low because children under two have not met the minimum food diversity and also minimum frequency of eating. Dietary diversity has also been shown to be strongly related to household socioeconomic status. Objectives: The purpose of this research was to analyze the socioeconomic factors associated with the diet quality of children aged 12-23 months. Methods: The research design was cross-sectional using secondary data analysis from the 2014 SKMI. The data used were subject characteristics, family socio-economic characteristics, and diet quality as measured by the dietary diversity consumption. The relationship factor analysis used is binary logistic regression. Results: Family socio-economic factors such as family size more than equal to 5 person (p=0,03: OR=1,4), high father's education (p=0.046; OR=1,1) low economic status (p=0.001; OR=2,2); medium economic status (p=0,005; OR=1,7) were related to the low diet quality of children aged 12-23 months, Improving family welfare in terms of education and economy needs to be done to improve the quality of food consumption for children under two years old.